Conceptual Creative Realism as a Methodological Model of Islamic Science: A Critical Review - Mohammad Reza Taghavi; Seyed Saeid Zahed (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The aim of the present study was a review of “Conceptual Creative Realism” as a methodological model of Islamic science (Iman & Kelateh Sadati, 1392). The model had some strong points including a new presentation of science structure as well as a new definition congruent with the Islamic point of view entered in a new paradigm. Besides, the model defined hierarchy of knowledge in different ways where the God’s laws would be at the top of this hierarchy. Reality is further up observations and objective experiences as well as the correct criterion defined according to Islamic direction. o On the contrary, the model had some drawbacks including speaking in general, not specified, and missing links between the different concepts, as well as having ambiguity responding how we can specify the borders between different knowledge sources such as sensation experiences, wisdom, and intuition. In sum, the evaluated model seems to be an effective model which contributes to the Islamic science.